2020
DOI: 10.1515/ael-2018-0037
|View full text |Cite
|
Sign up to set email alerts
|

Planetary Boundaries and Corporate Reporting: The Role of the Conceptual Basis of the Corporation

Abstract: There is a broad call to integrate planetary boundaries and life-cycle based reporting into accounting theory and reporting standards. Although many practitioners back this call, including insurers, shareholders with a long-term orientation, and company law specialists who suggest that the inclusion of long-term stakeholder interests is necessary to counter both corporate and systemic risks, it remains unanswered. We argue that dominant assumptions about the status and architecture of corporations in corporate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 77 publications
0
12
0
Order By: Relevance
“…Our review of the qualitative literature on context and regulation found 29 papers that considered NFR in particular contexts or regulatory settings. Of these, 13 were theoretical papers, dealing, for example, with the genealogical history of narrative reporting in the UK (Chahed, 2021), calling for harmonisation of NFR standards (Adams and Abhayawansa, 2022) or discussing the role of the modern corporation in accountability for NFR (Veldman and Jansson, 2020). Content analysis was a popular approach, with 11 papers exploring the impact of certain regulations or reporting changes on corporate reports, for example, the nature of IR reporting (Zinsou, 2018) or reports on national ESG policies (Camilleri, 2015).…”
Section: Context and Regulationmentioning
confidence: 99%
See 3 more Smart Citations
“…Our review of the qualitative literature on context and regulation found 29 papers that considered NFR in particular contexts or regulatory settings. Of these, 13 were theoretical papers, dealing, for example, with the genealogical history of narrative reporting in the UK (Chahed, 2021), calling for harmonisation of NFR standards (Adams and Abhayawansa, 2022) or discussing the role of the modern corporation in accountability for NFR (Veldman and Jansson, 2020). Content analysis was a popular approach, with 11 papers exploring the impact of certain regulations or reporting changes on corporate reports, for example, the nature of IR reporting (Zinsou, 2018) or reports on national ESG policies (Camilleri, 2015).…”
Section: Context and Regulationmentioning
confidence: 99%
“…While theory discovery studies start from preliminary theoretical developments and rely mainly on empirical insights, theory refinement studies frame on a more robust theoretical background. In the latter case, the researcher has selected which theoretical lens to use in investigating the research phenomenon (Vaivio, 2008). Qualitative research is suited to exploring complex causal relationships and subjective issues, investigating various interactions among variables with scant prior research, understanding how social actors use and react to accounting, and examining social change and developments in organisational behaviour (De Villiers, Dumay and Maroun, 2019).…”
Section: Qualitative Research Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…Lynn Stout did not live to see the unravelling of the doctrine of shareholder primacy and the potential abandonment of the maximisation of shareholder value as the central driver of US corporations, but this now does appear, to a degree at least, to be occurring in slow motion (Clarke, 2015;. The growing emergence of the Social License to Operate, the open debate on the Purpose of the Corporation (a company's fundamental reason for being), the revision of the core principle of the US Business Roundtable around corporate responsibility, and interest around the world in redefining the social and environmental obligations of corporations in the context of the devastating potential impact of climate change is beginning to suggest the absolute reign of shareholder primacy is coming to an end (Clarke, 2007;Veldman & Jansson, 2020).…”
Section: The Contest On Corporate Purposementioning
confidence: 99%